Pyrimethamine as a Potent and Selective Inhibitor of Acute Myeloid Leukemia Identified by High-throughput Drug Screening - Sharma, Amit; Jyotsana, Nidhi; K. Lai, Courteney; Chaturvedi, Anuhar; Gabdoulline, Razif; Görlich, Kerstin; Murphy, Cecilia; E. Blanchard, Jan; Ganser, Arnold; Brown, Eric; A. Hassell, John; Humphries, R. Keith; et al. (Current Cancer Drug Targets, 2016)
Hematopoietic stem and progenitor cell differentiation are blocked in acute myeloid leukemia (AML) resulting in cytopenias and a high risk of death. Most patients with AML become resistant to treatment due to lack of effective cytotoxic and differentiation promoting compounds. High MN1 expression confers poor prognosis to AML patients and induces resistance to cytarabine and alltrans-retinoic acid (ATRA) induced differentiation. Using a high-throughput drug screening, we identified the dihydrofolate reductase (DHFR) antagonist pyrimethamine to be a potent inducer of apoptosis and differentiation in several murine and human leukemia cell lines. Oral pyrimethamine treatment was effective in two xenograft mouse models and specifically targeted leukemic cells in human AML cell lines and primary patient cells, while CD34+ cells from healthy donors were unaffected. The antileukemic effects of PMT could be partially rescued by excess folic acid, suggesting an oncogenic function of folate metabolism in AML. Thus, our study identifies pyrimethamine as a candidate drug that should be further evaluated in AML treatment.
Keywords: High-throughput drug screening